Change Management Scope - Sonia Purba; Nuri Aslami (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Changes are made to the company to guarantee that it can attract and keep customers. HR managers must guarantee that any changes make it more likely for businesses to lose consumers. One of the most critical things HR managers must take is to improve communication in transformation projects. Communication can be crucial in establishing and implementing change initiatives. Change communication relies heavily on information sharing. Stakeholders must be aware of potential shifts in the timing, nature, and significance of business choices. Management participation at various levels is necessary to make change successful. Any organizational change necessitates HR managers ensuring that all levels of management are involved as change agents. Employees must be motivated to change and willing to accept the vision communicated by the organization's leadership for any change to be successful. It is easier to manage change efforts when HR managers provide evaluation or feedback to all members of the organization.